The Effectiveness of the Inside-Outside Circle Learning Model in Improving Students' Learning Motivation in Islamic Religious Education at Secondary Schools - Wardah Wardah; Moh. Sahlan; Indah Wahyuni (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
This study aims to examine the effectiveness of the Inside-Outside Circle (IOC) learning model in improving students' learning motivation in Islamic Religious Education at the junior secondary school level. This research employed a quantitative approach with a quasi-experimental non-equivalent control group design. The research sample consisted of 60 eighth-grade students at SMPN 1 Senduro, divided into an experimental group (n=30) and a control group (n=30). The experimental group was taught using the IOC model, while the control group received conventional teaching methods. Data were collected through a Likert-scale learning motivation questionnaire that had been tested for validity and reliability (α=0.87). Data analysis used a paired sample t-test and an independent sample t-test with a significance level of 5%. The results showed that the experimental group experienced an increase in motivation scores from 62.10 to 79.43, while the control group increased from 61.87 to 66.21. Statistical tests indicated a significant difference between the two groups (p < 0.05) with an effect size of 1.25 (large category). These findings indicate that the IOC model is effective in increasing students' learning motivation through structured interaction and active participation. This study recommends the implementation of the IOC model as an alternative for more interactive learning strategies in Islamic religious education.